UMKM: WUJUD KEMANDIRIAN EKONOMI PEREMPUAN MENUJU PEREKONOMIAN GLOBAL - Refti Handini Listyani; Ika Kharisma (Al'Adalah, 2016)
Entering the global economy, women in Indonesia still have to bear the burden of the economy in their household even a country. Moreover, they get inequality fee in their job. It means that men get more than women. However, on the other side, the role of women in a family and national economy is one of the important parts in the whole construction along with the increasing of women’s income. It is pointed by the presence of women entrepreneurs in micro, Small and Medium Enterprises (SME/UMKM) which becomes reality economic life in a considerable part of Indonesian people.